Respon Petani Terhadap Kebijakan Pompanisasi Pada Tanaman Padi (Oryza sativa) Sebagai Upaya Meningkatkan Produktivitas Lahan Pertanian Di Kecamatan Masbagik - Nurul Hakikah; Muhammad Anwar; Muhamad Sarlan; Rini Endang Prasetyowati (Jurnal Pertanian Khairun, 2025)
Rice production can be increased through the use of modern agricultural technology and farmer participation in implementing government policies. The purpose of this study was to analyze farmers' responses to the implementation of the pumping program as an effort to increase land productivity in Masbagik District, East Lombok Regency. Data were obtained through interviews guided by a questionnaire, then analyzed using a composite Likert scale score. The analysis showed that the majority of farmers in Masbagik District responded positively to the pumping optimization program. 52,5 percent of respondents rated the program as highly beneficial (very beneficial), 45.0% as moderate, and only 2.5% as very low. This reflects the program's effectiveness in supporting water availability, increasing productivity, and increasing planting time efficiency, making it worthy of being maintained and further developed.